Online counselling services: The future of counselling and psychotherapy, - Adebowale, Olusegun Fatai (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2023)
Purpose - The purpose of this paper is to stress the increasing imperativeness of counseling and psychotherapy in Nigerian universities, given the growing, strident, and persistent reports of maladaptive behaviors such as suicidal ideation and behaviors among university students.Method - The study employed the method of informed arguments to present online counseling as a veritable tool to assist the universities in linking the undergraduates with the sources of counseling and psychotherapy with the view to promoting their self-consciousness, self-understanding, and adequate mental health needed to develop top-level human resources.Result - It shares the experiences of online counseling interactions obtained from the Obafemi Awolowo University online counseling platform.Implication - Recommendations are also made to guide other universities in Nigeria and similar climes as to establishing their home-grown platform or sharing in the use of the existing dedicated platforms.Originality - The paper is one of the earliest to present an argument for including online counseling services in the systems of universities, particularly in the developing world. It is also the first to present a report of practical experiences garnered in such an established service in a Nigerian University to guide the establishment of more of such in other universities.***Tujuan - Tujuan dari makalah ini adalah untuk menekankan meningkatnya ketidaktegasan konseling dan psikoterapi di universitas-universitas di Nigeria, mengingat laporan yang terus meningkat, keras, dan terus-menerus mengenai perilaku maladaptif seperti ide dan perilaku bunuh diri di kalangan mahasiswa.Metode - Penelitian ini menggunakan metode argumen yang terinformasi untuk menyajikan konseling online sebagai alat yang tepat untuk membantu universitas dalam menghubungkan mahasiswa dengan sumber-sumber konseling dan psikoterapi dengan tujuan untuk meningkatkan kesadaran diri, pemahaman diri, dan kesehatan mental yang memadai yang diperlukan untuk mengembangkan sumber daya manusia tingkat atas.Hasil - Penelitian ini membagikan pengalaman interaksi konseling online yang diperoleh dari platform konseling online Universitas Obafemi Awolowo.Implikasi - Rekomendasi juga dibuat untuk memandu universitas lain di Nigeria dan negara lain yang memiliki iklim yang sama untuk membangun platform buatan sendiri atau berbagi penggunaan platform khusus yang sudah ada.Keaslian - Makalah ini adalah salah satu yang paling awal yang menyajikan argumen untuk memasukkan layanan konseling online ke dalam sistem universitas, terutama di negara berkembang. Makalah ini juga merupakan yang pertama yang menyajikan laporan tentang pengalaman praktis yang diperoleh dari layanan yang sudah mapan di Universitas Nigeria untuk memandu pendirian layanan serupa di universitas lain.